Myths’ shifting in the works of Haxhiademi: Array - Buzhala, Saranda (Acta Universitatis Danubius. Communicatio, 2021)
Etehem Haxhiademi is an Albanian author between the two world wars period. Based on his writings, we have seen him as the author of classical models of dramaturgy, and meanwhile his tragedies as subject taken from Albanian antiquity and the Middle Ages, from ancient mythology, as well as from the biblical one, who creates them by giving the spirit and the era in which he lives. This work is therefore focused mainly on these mythical models of Haxhiademi, which were observed with the help of the comparative method, sometimes also analytical. Even with the help of intertextual interpretations, very serious conclusions have been reached about the shifting and remodeling of the myths of Greek Antiquity, the biblical ones but also the Albanian myths by Haxhiademi. Through the confrontation of contrasts, Haxhiademi brings the classic model of tragedy in verse. We have seen that the myth is identified with the real historical events, that the author has mythologized the life and history and that at the same time replaces the mythical heroes in time and space. The fact that the tragedies of this author are extended beyond the Albanian borders, in the ideological and semantic aspect, shows that this work is of great interest to be considered as a comparative approach by literature-lovers.